“You are certainly my best friend” – Translating adverbs of evidential certainty in The Picture of Dorian Gray - Protopopescu Daria (Open Linguistics, 2023)
The present article focuses on the analysis of how adverbs of evidential certainty are translated into Romanian in Oscar Wilde’s The Picture of Dorian Gray. Drawing on previous work, we argue that adverbs of certainty exhibit different interpretations function of their context of occurrence and their position in the clause. In this analysis, I am going to look at the different translation strategies employed in the ten Romanian translations of the book. We are interested in investigating the differences between the earliest translation and the most recent retranslations. We can safely assume that evidentiality is a universal semantic category that is coded differently in different languages. Therefore, it is going to be interesting to see how the rendering of evidential adverbs into Romanian differs from one translator to another across time. Adverbs of certainty express more often than not a degree of confidence on the part of the speaker alongside the speaker’s attitude toward the content of the sentence.